Effects of air-polishing powders on color stability of composite resins - Ahmet Umut Güler; Ibrahim Duran; Ali Çağin Yücel; Pelin Özkan (University of São Paulo, 2011)
OBJECTIVES: The purpose of this study was to investigate the effect of different air-polishing powders on the color stability of different types of composite resin restorative materials. MATERIAL AND METHODS: Thirty cylindrical specimens (15×2 mm) were prepared for each of 7 composite resin restorative materials. All specimens were polished with a series of aluminum oxide polishing discs (Sof-Lex). The prepared specimens of each composite resin were randomly divided into 3 groups of 10 specimens each, for control (Group-C) and two air-powder applications (Group-CP: Cavitron Prophy-Jet; Group-PS: Sirona ProSmile prophylaxis powder). A standard air-polishing unit (ProSmile Handly) was used. All specimens were air-powdered for 10 s at 4-bar pressure. The distance of the spray nosel from the specimens was approximately 10 mm and angulation of the nosel was 90°. Specimens were stored in 100 mL of coffee (Nescafe Classic) for 24 h at 37°C. Color measurement of all specimens was recorded before and after exposure to staining agent with a colorimeter (Minolta CR-300). Color differences (∆E*) between the 2 color measurements (baseline and after 24 h storage) were calculated. The data were analyzed with a 2-way ANOVA test, and mean values were compared by the Tukey HSD test (p<0.05). RESULTS: According to the 2-way ANOVA results, composite resin restorative materials, air-polishing powders, and their interaction were statistically significant (p<0.05) For Aelite Aesthetic Enemal, Filtek Z250, Grandio, CeramX Mono, and Quixfil composite resin restorative materials, no significant difference was observed between Group-PS and Group-CP (p>.05) and these groups demonstrated the highest ∆E* values. For Filtek Silorane and IntenS, the highest ∆E* values were observed in Group-PS. The lowest ∆E* values for all composite resin groups were observed in Group-C. When comparing the 7 composite resin restorative materials, Aelite Aesthetic Enemal demonstrated significantly less ∆E* values than the other composite resins tested. The highest ∆E* values were observed in Quixfil. CONCLUSION: Except for Quixfil, all control groups of composite resins that were polished Sof-Lex exhibited clinically acceptable ∆E values (<3.7). Air-polishing applications increased the color change for all composite resin restorative materials tested. Composite restorations may require re-polishing after air-polishing.